Ochronotic Arthropathy: Two Case Reports from a Developing Country - Rathore, Farooq A. (Clin Med Insights Arthritis Musculoskelet Disord, 2016)
Alkaptonuria is a rare inborn error of metabolism, which is classified as an orphan disease. It is due to the lack of an enzyme homogentisate 1,2-dioxygenase, which results in an accumulation of homogentisic acid in different areas of the body, including sclera, skin, cardiac valves, articular cartilage of the large joints and intervertebral disks. We present two cases of alkaptonuria resulting in ochronotic arthropathy with advanced secondary generalized osteoarthritis, intervertebral disk calcifications, skin and scleral pigmentation. In these case reports, both patients had symptoms for >10 years before being diagnosed. Conservative management in the form of high-dose ascorbic acid, exercises, and gait aids was offered to both of them, which resulted in some symptomatic improvement in the first case, while the second case was lost to follow-up. Alkaptonuria is a rare disease, and although it does not clearly impact mortality, early diagnosis may improve the quality of life.